IMPLEMENTASI KNOWLEDGE MANAGEMENT DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN (Studi Pada Kantor BPJS Ketenagakerjaan Jawa Tengah dan DIY) - Irawan, Andrian Candra; Djastuti, Indi (Diponegoro Journal of Management, 2016)
This study aimed to analyze the influence of personal knowledge, job procedures and technology to employee's performance of BPJS Ketenagakerjaan Jawa Tengah and DIY.The population in this study were employees of the BPJS Ketenagakerjaan Jawa Tengah regional offices and branch offices Semarang 1 which consisted 64 people. The data were obtained by using the "saturation sampling/census" technique, in which all employees were the target of the sampling. The data that analyzed comes from distributing questionnaires to employees, then analyzed using multiple linear regression method with SPSS (Statistical Product and Service Solution) 16 program.The   analysis’   result   showed   that   the   variables:   personal   knowledge,   job procedures, technology positively influence on employee's performance. It means the better personal knowledge, job procedures, technology will improve the employee's performance. These variables contribute 49.4%. While the rest of 50.6% is explained by other variables.